Risk Assessment of Hazardous Healthcare Waste for the Hospital of an Algerian City - Linda, Sefouhi (Disease and Health Research: New Insights Vol. 5, 2024)
Algeria's economic and social development has generated large quantities of waste, including hazardous waste. Despite the efforts made and the legislation enacted, the management and treatment of this waste continue to present significant challenges. The production of these harmful materials has become a source of problems, not only of insalubrity but also of public health. Healthcare activities help to protect health, cure patients and save lives. But they also generate waste, approximately 20% of which represents an infectious, toxic, traumatic, or radioactive risk. The main problems concerning healthcare waste are a lack of awareness of health hazards, inadequate training in waste management, the absence of waste management and disposal systems, insufficient financial and human resources, and the low priority given to the issue. Inadequate management of healthcare waste is a serious concern in many developing countries due to the risks posed to human health and the environment. Poor management of health care wastes exposes healthcare workers, waste handlers and the community to different risks, including infections, toxic effects and injuries. Risk Management is a process for identifying hazards associated with a product, estimating and evaluating the associated risks, controlling these risks, and monitoring the effectiveness of the control. In Algeria, many efforts have been made by the government authorities in order to better manage the waste from healthcare facilities. However, most healthcare facilities do not comply with the principles stated in Algerian legislation. According to the Agence Nationale des Déchets (AND), the amount of healthcare waste generated in Algeria was around 35,000 t/year in 2018. The problem of managing this waste is acute, given the quantities generated and the lack of resources and specialized professional channels for its collection and treatment. In the hospital of Batna city, a total of about 1114 Kg of healthcare risk wastes are produced each day. The results indicated that the rate was 1.75 kg/bed/day which is higher than the national value of 0.72 kg/bed/day. However, waste management practices are not free from challenges. Thus, several injuries and infections associated with health care risk wastes were recorded in different services of the hospital of Batna. This study provides the Preliminary Hazard Analysis (PHA) for the Health Care Risk Waste (HCRW). This assessment tool is part of an overall strategy that aims at reducing the disease burden caused by poor healthcare waste management (HCWM) through the promotion of best practices of safety standards.